2021
DOI: 10.1371/journal.pone.0254376
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and genetic diversity of traditional varieties of agave in Hidalgo State, Mexico

Abstract: The agaves are plants of cultural importance which have been used by humans for about 10,000 years and about 40 specific uses. The most culturally and economically important of those uses are for the production of fermented (pulque) and distilled beverages (mescal). Pulque continues to be produced in nearly all of Mexico, and the agaves used for this purpose have shown domestication syndrome. We carry out an ethnobotanical, morphological, and genetic analysis of the traditional varieties of pulque agave used i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 40 publications
2
8
0
4
Order By: Relevance
“…The first PC was influenced mainly by the characteristics defining the plant size, including plant length, rosette diameter, the number of leaves, leaf length, and leaf width. These results are in accordance with the trends found in other Agave species used for producing fermented and distilled beverages, which confirms that an analysis of only vegetative characteristics is sufficient for distinguishing between Agave species [ 23 , 25 ]. On the other hand, the PCA also showed that the variables can clearly discriminate A. angustifolia individuals by their age, while A. potatorum plants were not so clearly defined.…”
Section: Discussionsupporting
confidence: 89%
“…The first PC was influenced mainly by the characteristics defining the plant size, including plant length, rosette diameter, the number of leaves, leaf length, and leaf width. These results are in accordance with the trends found in other Agave species used for producing fermented and distilled beverages, which confirms that an analysis of only vegetative characteristics is sufficient for distinguishing between Agave species [ 23 , 25 ]. On the other hand, the PCA also showed that the variables can clearly discriminate A. angustifolia individuals by their age, while A. potatorum plants were not so clearly defined.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, in the Agave genus, relatively high levels of inbreeding (FIS) have also been reported in other studies [43]. For example, considerable inbreeding was reported in wild and cultivated samples of A. maximiliana (FIS range from 0.002 to 0.32; [47]), in A. americana, A. salmiana and A. mapisaga (FIS ranged from 0.19 to 0.72 [68]) and in A. potatorum (FIS ranged 0.21-0.32; [75]).…”
Section: Inbreedingsupporting
confidence: 53%
“…The case of agave is probably more complicated, with some cultivated varieties (e.g., A. tequilana, A. salmiana and A. americana) presenting low levels of diversity [40,48,67,68] , whereas in other species levels of genetic variability are indistinguishable or even higher in cultivated individuals in comparison to their wild counterparts [43,47]. Here, we found that cultivated individuals of A. angustifolia in northwestern Mexico have not lost genomic diversity, nor did they present increased inbreeding in comparison to their wild counterparts.…”
Section: Genetic Diversitymentioning
confidence: 99%
“…The case of agave is probably more complicated, with some cultivated varieties (e.g., A. tequilana, A . salmiana and A. americana ) presenting low levels of diversity [ 46 , 54 , 71 , 72 ], whereas in other species levels of genetic variability are indistinguishable or even higher in cultivated individuals in comparison to their wild counterparts [ 49 , 53 ]. Here, we found that cultivated individuals of A. angustifolia in northwestern Mexico have not lost genomic diversity, nor did they present increased inbreeding in comparison to their wild counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…salmiana and A . mapisaga ( F IS ranged from 0.19 to 0.72 [ 72 ]) and in A. potatorum ( F IS ranged 0.21–0.32; [ 78 ]).…”
Section: Discussionmentioning
confidence: 99%